If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y(3y + 8) = -5 Reorder the terms: y(8 + 3y) = -5 (8 * y + 3y * y) = -5 (8y + 3y2) = -5 Solving 8y + 3y2 = -5 Solving for variable 'y'. Reorder the terms: 5 + 8y + 3y2 = -5 + 5 Combine like terms: -5 + 5 = 0 5 + 8y + 3y2 = 0 Factor a trinomial. (5 + 3y)(1 + y) = 0Subproblem 1
Set the factor '(5 + 3y)' equal to zero and attempt to solve: Simplifying 5 + 3y = 0 Solving 5 + 3y = 0 Move all terms containing y to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 3y = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 3y = 0 + -5 3y = 0 + -5 Combine like terms: 0 + -5 = -5 3y = -5 Divide each side by '3'. y = -1.666666667 Simplifying y = -1.666666667Subproblem 2
Set the factor '(1 + y)' equal to zero and attempt to solve: Simplifying 1 + y = 0 Solving 1 + y = 0 Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + y = 0 + -1 Combine like terms: 1 + -1 = 0 0 + y = 0 + -1 y = 0 + -1 Combine like terms: 0 + -1 = -1 y = -1 Simplifying y = -1Solution
y = {-1.666666667, -1}
| (r/-7)-5=-6 | | 3x+4=(x-8) | | 2y+8=10y | | w^2-14w-72=0 | | c=5(F-32)/9 | | 60x^2-44x-5= | | -24+6=-5 | | -10x-3x-3x=-70 | | (3x-6)(5x-9)= | | 3x/4-1 | | 2x^3=35 | | x+2x+x+27=167 | | -630=76x+126y | | 7.5+0.5x=3/4x | | 3r^2+r-24=0 | | 9x+2y=36 | | 4t^2-3t-5=0 | | -8x-7x=64 | | 5x-10+5x=-10 | | 5x-3=3x-11 | | -3x-7y=21 | | x+x^2=x^3 | | (9-2x)2=0 | | 8y+9x=36 | | -3x+5=11 | | 0.5(x+2)=0.1+3(0.1+0.3) | | in(7x+4)=1 | | 1/4+1/13-1/52 | | 2x/3y^2.6y/4x | | 2x/3y2.6y/4x | | x*5=84 | | 81x^2+16=0 |